Analisis Aspek Leksikal dalam Talk Show Sentilan-Sentilun Edisi “Perpustakaan DPR Untuk Siapa?” - Juni Mahsusi (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research aims to describe what lexical aspects are used in Sentilan Sentilun's discourse “DPR Library for whom?” and what is most dominantly used in the discourse. This research uses a descriptive qualitative method with a discourse analysis technique. The data source in this research is Sentilan Sentilun's program "DPR Library For Whom?”. The results of this study found several lexical aspects including repetition, synonymy, antonymy, hyponymy, collocation, and equivalence. The linguistic aspects that dominantly appear are lexical aspects of repetition and equivalence. Lexical aspects of repetition such as reading books, reading interest and reading mean literacy awareness conveyed in satire to DPR members. In addition, the meaning of repetition such as father and minister also dominates the meaning of respectful greetings. In the lexical aspect of equivalence, the affixation process of basic words such as read, wake up, and believe shows the meaning of the equivalence of words in speech.